Psychological Impact of the COVID-19 Pandemic on Pregnant Women - Buonsenso, Danilo; Malorni, Walter; Turriziani Colonna, Arianna; Morini, Sofia; Sbarbati, Martina; Solipaca, Alessandro; Di Mauro, Antonio; Carducci, Brigida; Lanzone, Antonio; Moscato, Umberto; Costa, Simonetta; Vento, Giovanni; et al. (Frontiers in Pediatrics, 2022)
Objective The aim of this study is to assess the impact of the COVID-19 pandemic on mental health, type of delivery, and neonatal feeding of pregnant women with or without SARS-CoV-2 infection during gestation. Study Design The study was conducted online, and anonymous survey was distributed to mothers that delivered during the COVID-19 pandemic. Results The survey was completed by 286 women, and 64 women (22.4%) had COVID-19 during pregnancy. Women that had SARS-CoV-2 infection during pregnancy or at time of delivery had a significantly higher probability of being separated from the newborn (p < 0.0001) and a significantly lower probability of breastfeeding (p < 0.0001). The Edinburg Postnatal Depression Scale, to assess if mothers had symptoms of postnatal depression, showed that items suggestive of postnatal depression were relatively frequent in the whole cohort. However, women with SARS-CoV-2 infection during pregnancy reported higher probability of responses suggestive of postnatal depression in eight out of 10 items, with statistically significant differences in three items. Conclusion The COVID-19 pandemic affected the type of delivery and breastfeeding of pregnant women, particularly when they had SARS-CoV-2 infection. This, in turn, had an impact on the psychological status of the interviewed mothers, aspects that could benefit of special support.